2012
DOI: 10.1158/2159-8290.cd-11-0189
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the 14-3-3σ Tumor Suppressor Is a Critical Event in ErbB2-Mediated Tumor Progression

Abstract: is a putative tumor suppressor involved in cell-cycle progression and epithelial polarity. We demonstrate that loss of one or both copies of the conditional 14-3-3σ allele results in accelerated mammary and salivary tumorigenesis in mice expressing an activated erbB2 oncogene under the endogenous erbB2 promoter. Significantly, the majority of tumors bearing a single conditional 14-3-3σ allele lose expression of the remaining 14-3-3σ allele, which is associated with epigenetic methylation of the 14-3-3σ locus. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
(56 reference statements)
2
20
0
Order By: Relevance
“…53). Given the previous reports linking 14-3-3σ with polarity and metastasis suppression in HER2 + mouse mammary gland cancer models (17,18), our data suggest that the functions of this intriguing protein are contingent on the cancer subtype. In agreement with prior reports, we observed only 6% (2 of 28) of HER2 + tumors retained detectable 14-3-3σ expression (Table 1).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…53). Given the previous reports linking 14-3-3σ with polarity and metastasis suppression in HER2 + mouse mammary gland cancer models (17,18), our data suggest that the functions of this intriguing protein are contingent on the cancer subtype. In agreement with prior reports, we observed only 6% (2 of 28) of HER2 + tumors retained detectable 14-3-3σ expression (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…13 and the current study) identified 14-3-3σ (also known as stratifin, SFN) as a protein expressed at higher levels in malignant T4-2 cells relative to its nonmalignant S1 counterpart. The finding that 14-3-3σ expression followed HMT-3522 malignant progression was surprising, given that this molecule is described broadly as a tumor suppressor; in the breast, it is frequently down-modulated through promoter methylation or proteolysis (the latter particularly in ER-positive tumors) (14)(15)(16), and it has been shown also to regulate cell polarity through Par3 association and suppress metastasis in mouse models of HER2-positive mammary cancer (17,18). Additionally, 14-3-3σ functions as an enforcer of the G 2 /M checkpoint in HCT116 colorectal cancer cells by sequestering cyclin B1 and cdc2 from the nucleus (19,20) and facilitates mitotic translation in HeLa and U2OS cells (21).…”
mentioning
confidence: 99%
“…Although many of the signaling pathways involved in breast tumors have been elucidated, others are still being discovered. After many years of speculation that polarity disruption is fundamental to cancer, recent data have confirmed that defects in the epithelial polarity machinery accelerate solid tumor progression in mammals (2)(3)(4)(5)(6). The mechanisms by which polarity restrains tumor progression remain largely unknown.…”
mentioning
confidence: 99%
“…Three polarity networks are highly conserved in mammalian cells: the Par complex, consisting of PAR3, PAR6, and atypical protein kinase C (aPKC), 2 is situated at tight junctions and the apical surface; the Crumbs complex, containing Crumbs (CRB), PALS1, and PATJ, is essential for specifying the apical membrane; and a group of proteins that includes Scribble (SCRB), Discs-large (DLG), and Lethal Giant Larvae (LGL), localize to the basolateral membrane (7). Members of all three groups have been implicated in tumorigenesis, although mainly through correlative evidence (6, 8 -13).…”
mentioning
confidence: 99%
“…What can we learn about 14-3-3σ's role as a tumor suppressor in the article by Ling and colleagues (5) in this issue? First, we need to provide some information on the transgenic models that were used.…”
mentioning
confidence: 99%